2018
DOI: 10.7717/peerj.5709
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure of the pelagic mollusk Limacina helicina in the Kara Sea

Abstract: BackgroundPelagic pteropods Limacina helicina are widespread and can play an important role in the food webs and in biosedimentation in Arctic and Subarctic ecosystems. Previous publications have shown differences in the genetic structure of populations of L. helicina from populations found in the Pacific Ocean and Svalbard area. Currently, there are no data on the genetic structure of L. helicina populations in the seas of the Siberian Arctic. We assessed the genetic structure of L. helicina from the Kara Sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Questel et al (2016) found no evidence of population structure based on mtCOI for copepod species of Pseudocalanus, and recent studies using mitochondrial and microsatellite makers concluded that Arctic populations of the copepod C. glacialis are panmictic (Weydmann et al, 2016(Weydmann et al, , 2018, but see Nelson et al (2009). Patterns of COI haplotype diversity also supported Pan-Arctic dispersal of the pteropod Limacina helicina, with evidence of population expansion during Pleistocene glaciation (Abyzova et al, 2018).…”
Section: Population Genetic Diversity Structure Connectivity Based On...mentioning
confidence: 98%
“…Questel et al (2016) found no evidence of population structure based on mtCOI for copepod species of Pseudocalanus, and recent studies using mitochondrial and microsatellite makers concluded that Arctic populations of the copepod C. glacialis are panmictic (Weydmann et al, 2016(Weydmann et al, , 2018, but see Nelson et al (2009). Patterns of COI haplotype diversity also supported Pan-Arctic dispersal of the pteropod Limacina helicina, with evidence of population expansion during Pleistocene glaciation (Abyzova et al, 2018).…”
Section: Population Genetic Diversity Structure Connectivity Based On...mentioning
confidence: 98%
“…To examine the phylogenetic relationships, haplotype networks were drawn in PopArt 1 using the TCS (Templeton et al, 1992) network approach (95% parsimony connection limit) with the algorithm described by Clement et al (2002) to determine the ancestral haplotype according to the neutral coalescent theory. The haplotypes were grouped into haplogroups based on the number of mutational steps and abundant haplotypes connected to several singletons (see Abyzova et al, 2018) as well as the Bayesian inference of phylogeny. The frequencies of each haplogroup were calculated for each sample site and transformed into pie charts on the map (see Figure 2).…”
Section: Genetic Diversity and Haplotype Parsimony Networkmentioning
confidence: 99%
“…Global haplotype divergence was small, with most haplotypes differing from each other by a few mutations (Supplementary Figure 3). However, two previously described haplogroups (Abyzova et al, 2018;Shimizu et al, 2018) described the data, with evidence of a unique haplogroup limited to Svalbard and the Kara Sea, and dominance of the second haplogroup in the Bering Sea, Amundsen Gulf and North Pacific Seas. While the haplogroups differ by only a few mutations, these data suggests separate colonization and divergence events and broad-scale population structure.…”
Section: Genetic Analysesmentioning
confidence: 60%